2014
DOI: 10.1016/j.cis.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The formation of host–guest complexes between surfactants and cyclodextrins

Abstract: Cyclodextrins are able to act as host molecules in supramolecular chemistry with applications ranging from pharmaceutics to detergency. Among guest molecules surfactants play an important role with both fundamental and practical applications. The formation of cyclodextrin/surfactant host-guest compounds leads to an increase in the critical micelle concentration and in the solubility of surfactants. The possibility of changing the balance between several intermolecular forces, and thus allowing the study of, e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
99
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(106 citation statements)
references
References 326 publications
(255 reference statements)
5
99
0
2
Order By: Relevance
“…The beneficial modification of guest molecular properties after the formation of the inclusion complex leads to a large number of applications in areas as diverse as encapsulation of active substances (i.e., flavoring agents, metallic cations, fragrances, and pesticides), enzymatic synthesis, catalysis, and energy transfer studies [3,4]. Additionally, CDs also find important uses in cosmetics, environment protection, bioconversion, packing, textiles, and food domain [1,5].…”
Section: Cyclodextrins: General Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The beneficial modification of guest molecular properties after the formation of the inclusion complex leads to a large number of applications in areas as diverse as encapsulation of active substances (i.e., flavoring agents, metallic cations, fragrances, and pesticides), enzymatic synthesis, catalysis, and energy transfer studies [3,4]. Additionally, CDs also find important uses in cosmetics, environment protection, bioconversion, packing, textiles, and food domain [1,5].…”
Section: Cyclodextrins: General Considerationsmentioning
confidence: 99%
“…The effect of the length of the alkyl chain and surfactant head group on the association constant of APGs with different CDs was studied by 1 H NMR spectroscopy, NMR selfdiffusion, and surface tension ( Table 1) [58][59][60]. Although the comparison between association constants computed on the basis of different physical parameters is a difficult task [5], the analysis of the data allowed concluding that by increasing the alkyl chain length and decreasing the CD cavity volume (from β-toα-CD), the association constant increases. Furthermore, some authors stated that no interactions were observed when γ-CD was used [59,58].…”
Section: Interaction Between Alkyl Polyglycosides and Cyclodextrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixed cyclodextrin-surfactants systems combine the characteristics of composing species and also have many features compared to conventional single systems. [15] Therefore, in this paper we would like to construct the supramolecular systems based on β-cyclodextrin (β-CD) and ionic surfactant with oxime-counterion for effective hydrolysis of paraoxon (POX) being one of the most potent acetylcholinesterase-inhibiting pesticides. Since the cationic oxime pralidoxime (2-PAM) was taken as a surfactant counterion, the anionic sodium dodecyl sulfate (SDS) was chosen as a surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…The solutions undergo micellar growth and micelle to vesicle transitions. Moreover, β-cyclodextrin is also important towards controlling the thicknesses of hydropho-bically modified polymers, e.g., ethyl(hydroxyl ethyl) cellulose and modified poly(ethylene glycol) in water by decoupling hydrophobic-hydrophobic intermolecular interactions [22,23]. Hence, the orientation of the β-cyclodextrin-surfactant com-plexes in the CPE is suitable towards the cooperative binding of the analyte recoveries.…”
mentioning
confidence: 99%